Vehicle Routing, Scheduling and Decision Utility Environment - Ozgur, Ceyhun; Okkema, Claire; Shen, Yiming (Advances in Social Sciences Research Journal, 2018)
In this paper, we will try to summarize research on vehicle scheduling and decision utility. We assume a given framework with centralized management distribution system replenishment and given sets of distribution centers. We provide a solution to the issues of how vehicles can be scheduled or routed to achieve a company’s logistic objectives. The problem, as typically formulated, is to determine the order turn in which the customers will be visited by delivery or pick-up vehicles otherwise called the route. Lastly, we discuss the facets of priority class scheduling in decision utility management and its advantages.